Key to species of the genus Longicornus Li & Song (Hemiptera: Cicadellidae: Deltocephalinae) with description of a new species - Gou, Guangli; Xing, Jichun (Zootaxa, 2022)
A new leafhopper species: Longicornus grossus sp. nov., is described and illustrated from Yunnan Province, China. A key based on the aedeagus is given to distinguish all species of the genus. The type specimens of the new species are deposited in the Institute of Entomology, Guizhou University, Guiyang, China (GUGC).